1976
DOI: 10.1063/1.89041
|View full text |Cite
|
Sign up to set email alerts
|

Thin-film CuInSe2/CdS heterojunction solar cells

Abstract: The fabrication procedures and characteristics of several thin-film p-CuInSe2/n-CdS heterojunction solar cells are presented. Two modes of operation (illumination through CuInSe2 or through CdS) are discussed. Efficiencies in the range of 4–5% are reported, under 100 mW/cm2 tungsten-halogen illumination for 1.2-cm2 devices. Included are the spectral response and J-V characteristics for these photovoltaic junctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(68 citation statements)
references
References 8 publications
1
66
0
1
Order By: Relevance
“…The properties of several I-III chalcopyrite compounds are also suitable for photovoltaic applications and amongst them the most promising include copper-indium-diselenide (CuInSe 2 ) often called CIS, copper-gallium-diselenide (CuGaSe 2 ) called CGS, their mixed alloys copper-indium gallium-diselenide (Cu(In,Ga)Se 2 ) called CIGS and copper-indiumdisulfide (CuInS 2 ). The first PV devices of copper chalcopyrite appeared in 1976 (Kazmerski et al, 1976) and since then it was not until the early 1990s that rapid improvements increased efficiencies to over 16 % (Gabor et al, 1994). Even though the commercial production of CIGS began in 2007, there are now a number of companies with 10 -30 MW/year capacities (Wolden et al, 2011).…”
mentioning
confidence: 99%
“…The properties of several I-III chalcopyrite compounds are also suitable for photovoltaic applications and amongst them the most promising include copper-indium-diselenide (CuInSe 2 ) often called CIS, copper-gallium-diselenide (CuGaSe 2 ) called CGS, their mixed alloys copper-indium gallium-diselenide (Cu(In,Ga)Se 2 ) called CIGS and copper-indiumdisulfide (CuInS 2 ). The first PV devices of copper chalcopyrite appeared in 1976 (Kazmerski et al, 1976) and since then it was not until the early 1990s that rapid improvements increased efficiencies to over 16 % (Gabor et al, 1994). Even though the commercial production of CIGS began in 2007, there are now a number of companies with 10 -30 MW/year capacities (Wolden et al, 2011).…”
mentioning
confidence: 99%
“…Its ternary zinc-blende alloys such as MgCdTe and MgZnTe have been considered as potential candidates for low-cost, high efficiency, multi-junction thin film solar cell materials to complement existing CdTe and Cu(In,Ga)Se 2 solar materials [1][2][3] . The use of these alloys for high efficiency solid-state light-emission devices has also attracted much attention [4][5][6] .…”
mentioning
confidence: 99%
“…Subsequent studies [82,83] showed evidence of significant optical absorption at energies below this fundamental absorption edge. Characterization of polycrystalline CIS absorber films suitable for devices almost always indicate a significantly lower effective bandgap of ~0.90 eV [84], apparently a consequence of significant collection of carriers generated by absorption in these band-tails. It has been suggested that the widely reported variations in the optical properties of CIS materials are a direct consequence of variations in composition [85].…”
Section: Optical Properties Of Ternary Cu-iii-vi Materialsmentioning
confidence: 99%